International opinions and national surveillance suggest insufficient consensus regarding the recognition and management practices of infants with congenital cytomegalovirus infections. (29th May 2017) - Gunkel, J; Nijman, J; Verboon‐Maciolek, MA; Wolfs, TFW; de Vries, LS
Abstract: Aim: This study evaluated the recognition and management practices with regard to congenital cytomegalovirus (cCMV) infections by a select group of experts and through a national surveillance study. Method: A questionnaire was sent to international experts involved in mother and infant care in 2014–2015. Monthly surveillance was conducted among Dutch paediatricians for cases of cCMV infections from 2013 until 2015. Results: The questionnaire was completed by 63/103 (62%) respondents, who indicated that recognition and management practices varied. Maternal screening was performed by 17/63 (27%) and infant screening by 3/61 (5%) of the respondents. Infant CMV diagnostics were most frequently initiated due to hepatosplenomegaly and/or an increase in liver transaminases. Management practices included cranial ultrasound (57/63, 91%) and audiological follow‐up in symptomatic (61/63, 97%) and asymptomatic (52/63, 83%) infants. In terms of antiviral treatment, 46/63 (73%) treated symptomatic infants only and 6/63 (9%) treated all infected infants. In total, 48 cases were registered through the Dutch surveillance study and 43/48 (90%) infants were symptomatic. Conclusion: This study indicates that infants with cCMV infection were insufficiently recognised and highlights the need for consensus on management practices. Screening of infants and the development of an international management guideline are recommended.